Analysis of online quizzes as a teaching and assessment tool - Lorenzo Salas-Morera; Antonio Arauzo-Azofra; Laura García-Hernández (OmniaScience, 2012)
This article deals with the integrated use of online quizzes as a teaching and assessment tool in the general program of the subject Proyectos in the third course of Ingeniero Técnico en Informática de Gestión over five consecutive years. The research undertaken aimed to test quizzes effectiveness on student performance when used, not only as an isolated assessment tool, but also when integrated into a combined strategy, which support the overall programming of the subject. The results obtained during the five years of experimentation using online quizzes shows that such quizzes have a proven positive influence on students' academic performance. Furthermore, surveys conducted at the end of each course revealed the high value students accord to use of online quizzes in course instruction.